IMPLEMENTASI PEMBELAJARAN IPA BERBASIS DARING DI SD NEGERI KARANG JADI - Haryati, Siti; Rezkita, Shanta; Rahayu, Ayu (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to describe online-based science learning at SD Negeri Karang Jadi in the odd semester of the 2020/2021 academic year, both the obstacles experienced by teachers and students and the efforts made by teachers to overcome obstacles during the online science learning process. The research method is qualitative. The research subjects included principals, teachers, and high-grade students of SD Negeri Karang Jadi Ogan Komering Ulu Timur. Data collection techniques through interviews, observation, and supported by documentation. The research instrument used interview, observation, and documentation methods. The data analysis technique uses inductive analysis which includes data reduction, data presentation, and concluding. The data validity technique used source triangulation, technique triangulation, and time triangulation. The results of the study indicate the following. First, online-based science learning at SD Negeri Karang Jadi Ogan Komering Ulu Timur in the odd semester of the 2020/2021 academic year has been implemented even though it has not been able to run optimally. Online-based science learning is carried out through the WhatsApp Group application, YouTube, and google forms. The two obstacles experienced by teachers and students are: constraints on the internet network; cost constraints to buy internet quotas; limited facilities and infrastructure used for online learning; limited ability to use technology owned by teachers, students, and parents, participants; students have difficulty understanding the material. The third attempt is to overcome the obstacles faced during the online learning process, namely by conducting home visit learning and using interesting learning videos on YouTube.